Lactic acid and cognitive function: Investigations in female volleyball athletes - Lardika, Rola Angga; Tarigan, Beltasar; Ray, Hamidie Ronald Daniel; Yudiana, Yunyun (UIR Press, 2023)
Lactic acid is a by-product of anaerobic metabolism and is commonly associated with muscle fatigue. However, recent research suggests that lactic acid may also positively affect cognitive function. Thus, this study aimed to investigate the relationship between lactic acid and cognitive function in female volleyball athletes. The study involved 12 female volleyball players from the Student Education and Training Centre (PPLP) of Riau Province, and a total sampling method was utilised. Data collection involved cognitive function tests using the Concentration Grid Test (CGT) instrument and lactic acid measurements using Accutrend lactate. The results revealed a significant correlation between lactic acid and cognitive function, with athletes with higher lactic acid levels after the training session performing better on cognitive tests. This suggests that lactic acid may enhance cognitive function by increasing glucose availability, which serves as the brain’s primary energy source. However, it is essential to consider the potential negative effects of excessive lactic acid levels, such as muscle fatigue, breakdown, and lactic acidosis, on both of the body and brain. Despite demonstrating the role of lactic acid in cognitive function among female volleyball athletes, caution must be exercised to prevent undue lactic acid production. Overall, this study provides valuable insight into the intricate relationship between lactic acid and cognitive function, which has implications for optimising cognitive ability in female volleyball athletes and potentially in other professional sports. Future research is needed to establish optimal lactic acid levels for cognitive function in diverse athletic contexts.